JURIDICAL ANALYSIS OF PUBLIC INFORMATION DISCLOSURE RELATED TO CONTRACTS ON PUBLIC AND PRIVATE PARTNERSHIPS - Purbawati, Retno; Irianti Topon, Yunita; Kabida Mumtaza, Fielsa; Rahman, Arif (Kertha Semaya : Journal Ilmu Hukum; Vol 11 No 12 (2023)DO - 10.24843/KS.2023.v11.i12.p12, 2023)
The purpose of this study is to explore the openness of contracts for Public and Private Partnership (PPP) in civil law and legal aspects of state administration. The type of research used is normative juridical, with an approach to laws and regulations ( statute approach ), conceptual approach ( conceptual approach ), and the case approach ( the case approach ). The study results show that the position of contract documents in relation to public information disclosure on civil law and state administration legal aspects has not demonstrated consistent provisions. In the civil aspect, the contract is binding only for the parties in it. Meanwhile, in state administrative law, the implementation of Public and Private Partnership (PPP) contracts that affect the community is precisely related to openness which becomes an urgency as a manifestation good governance and transparency as the embodiment of the General Principles of Good Governance. Legal certainty is an urgency to be realized.